The Nucleus: Heart of the Atom - Lindenfeld, Peter; Brahmia, Suzanne White; White Brahmia, Suzanne (Physics, 2011)
In 1896 Henri Becquerel wrapped a photographic plate so that no light could get to it together with a uranium compound outside the package. It was to be an experiment on x-rays, which had been discovered by Röntgen a few weeks earlier. He meant to investigate the possibility that sunlight would somehow stimulate the uranium to emit x-rays, which would then pass through the packaging and expose the plate, so that it would be darkened after being developed. The darkening did indeed take place, but did so even in the absence of any light on the uranium. Becquerel’s hypothesis was